1998
DOI: 10.1111/j.1440-1827.1998.tb03909.x
|View full text |Cite
|
Sign up to set email alerts
|

Extrauterine low‐grade endometrial stromal sarcoma: Report of three cases

Abstract: Three cases of rare low-grade endometrial stromal sarcoma of the extrauterine tissue are presented. Each one occurred in the ovary, pelvic and abdominal cavities. Two were associated with endometriosis. Histologically, the tumors were characterized by an infiltrative and diffuse proliferation of uniform round or oval cells, abundant small vessels, low mitotic activity, the presence of foam cells and vascular invasion. Immunohistochemically, all tumors expressed vimentin, muscle markers (desmin, muscle-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Therefore, it is reasonable to suggest that ESS arising from endometriosis should be considered in the differential diagnosis of a pelvic mass in patients with highly elevated CA125 levels together with a history of endometriosis. Nevertheless, data with regard to serum CA125 levels in patients with ESS arising from endometriosis are limited and are currently only available in 7 published case reports [2,24,29,30,31,35,37]. More studies to estimate the value of the CA125 level in ESS arising from endometriosis are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is reasonable to suggest that ESS arising from endometriosis should be considered in the differential diagnosis of a pelvic mass in patients with highly elevated CA125 levels together with a history of endometriosis. Nevertheless, data with regard to serum CA125 levels in patients with ESS arising from endometriosis are limited and are currently only available in 7 published case reports [2,24,29,30,31,35,37]. More studies to estimate the value of the CA125 level in ESS arising from endometriosis are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, ESS arising from endometriosis is a rarer disease with an incompletely understood etiology. Previous studies have usually been based on case reports, and no more than 50 cases of ESS arising in endometriosis have been reported in the English literature (table 3) [2,4,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. In the current study, we reported the clinicopathological features of a series of 5 cases treated in our center, including the results of expression analyses for several possible markers for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between hormonal therapy, especially unopposed estrogens, and the development of ESS (and other neoplasms) in endometriosis. [39][40][41] Unopposed estrogens are contraindicated in post-hysterectomy patients with a history of endometriosis. Before making a diagnosis of a primary ovarian (or any extrauterine) ESS, a primary uterine neoplasm should be excluded.…”
Section: Ovarian Endometrial Stromal Sarcomamentioning
confidence: 99%
“…30 ESS is more common in extraovarian endometriosis than in ovarian lesions, possibly reflecting the increased hormone sensitivity of the pelvic peritoneum vs. the ovary. 31,32 This finding could also reflect the tissue preference of cells.…”
Section: Histology Of Endometriosis-related Malignant Conditionsmentioning
confidence: 99%